ANALISIS MUTU PELAYANAN PETUGAS FARMASI DAN KETERSEDIAAN OBAT TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RS SANTA CLARA MADIUN TAHUN 2019 - Nurcahyani, Diah; Kartikaningrum, Vidya (Widya Warta, 2019)
Service quality, pharmaceutical providers, and the availability of medicines determine the outpatients’ satisfaction in the Department of Hospital Pharmaceutical Installation (IFRS). The phenomena, found in RS Santa Clara Madiun, are that and patients usually wait too long to get medicines, and the presence of empty drugs. The objective of the research was to find out the influence of the service quality pharmaceutical providers and the availability of medicines on the outpatients’ satisfaction in RS Santa Clara, in June 2019h . The research was a cross sectional method on 100 outpatients, using accidental sampling technique. The data were gathered by using questionnaires and analyzed by using bilinear regression test (α= 0,05). The result of the research showed that the variables of pharmaceutical providers and the availability of medicines influenced patients’ satisfaction (p < 0.005). The variable of the availability of medicines had the most dominant influence on outpatients’ satisfaction at the coefficient value of (β) 0.853). It is recommended that the management of RS Santa Clara Madiun furnish the availability of medicines and the facility of the IFRS waiting rooms, and pharmaceutical providers increase the dimension of the guarantee in order to improve the performance of the pharmaceutical providers and the information service about medicines.